An overdetermined problem of the biharmonic operator on Riemannian manifolds - Fan Chen; Qin Huang; Qihua Ruan (Boundary Value Problems, 2023)
Abstract Let ( M , g ) $(M,g)$ be an n-dimensional complete Riemannian manifold with nonnegative Ricci curvature. In this paper, we consider an overdetermined problem of the biharmonic operator on a bounded smooth domain Ω in M. We deduce that the overdetermined problem has a solution only if Ω is isometric to a ball in R n $\mathbb{R}^{n}$ . Our method is based on using a P-function and the maximum principle argument. This result is a generalization of the overdetermined problem for the biharmonic equation in Euclidean space.